From macroplastics to microplastics: Role of water in the fragmentation of polyethylene. (December 2019) - Julienne, Fanon; Delorme, Nicolas; Lagarde, Fabienne
Abstract: In this work, the artificial photodegradation of polyethylene films was studied in laboratory to compare the fragmentation pathways of this polymer at air and in water. Oxidation, surface mechanical properties, crystallinity and crack propagation were monitored to investigate their influence on fragmentation. Without any external stress, fragmentation only occurred in water despite a higher level of oxidation for films weathered at air. The cracking of the films did not appear correlated with the oxidation level and the presence of water appeared as a promoter of cracking propagation. The results also showed that the mechanical properties at the surface play a major role in the fragmentation pathway whereas the fabrication process may influence the propagation direction of the cracks. Consequently, the distribution in size of plastic fragments in the aquatic environment may be linked to the nature of the polymer but also to its manufacturing process. In this study, after 25 weeks of weathering in water, 90% of the fragments were >1 mm with very similar shapes showing that micrometric fragments were not yet abundant. These results suggest that long times of weathering in water and many steps of fragmentation appear necessary from macroplastics to reach sizes <1 mm in the aquatic environment. These results constitute a first attempt to understand the pathways leading from macroplastics to microplastics in water. They have to be confirmed for other polymers and the long-term behavior of the fragments needs to be studied to predict their decrease in size among time. Highlights: Fragmentation of polyethylene films into microplastics were studied in water and at air. The cracking of films did not appear correlated with the oxidation level. The presence of water appeared as a promoter of cracking propagation. The mechanical properties and the fabrication process play a major role in the fragmentation and influence the distribution in size of fragments. Many steps of fragmentation appear necessary from PE macroplastics to reach microplastics in the aquatic environment.